Enhancing endogenous levels of GLP1 dampens acute olanzapine induced perturbations in lipid and glucose metabolism - Medak, Kyle D.; Weber, Alyssa J.; Shamshoum, Hesham; McKie, Greg L.; Hahn, Margaret K.; Wright, David C. (Frontiers in Pharmacology, 2023)
Olanzapine is a second-generation antipsychotic (SGA) used in the treatment of schizophrenia and several on- and off-label conditions. While effective in reducing psychoses, acute olanzapine treatment causes rapid hyperglycemia, insulin resistance, and dyslipidemia and these perturbations are linked to an increased risk of developing cardiometabolic disease. Pharmacological agonists of the glucagon-like peptide-1 (GLP1) receptor have been shown to offset weight-gain associated with chronic SGA administration and mitigate the acute metabolic side effects of SGAs. The purpose of this study was to determine if increasing endogenous GLP1 is sufficient to protect against acute olanzapine-induced impairments in glucose and lipid homeostasis. Male C57BL/6J mice were treated with olanzapine, in the absence or presence of an oral glucose tolerance test (OGTT), and a combination of compounds to increase endogenous GLP1. These include the non-nutritive sweetener allulose which acts to induce GLP1 secretion but not other incretins, the DPPiv inhibitor sitagliptin which prevents degradation of active GLP1, and an SSTR5 antagonist which relieves inhibition on GLP1 secretion. We hypothesized that this cocktail of agents would increase circulating GLP1 to supraphysiological concentrations and would protect against olanzapine-induced perturbations in glucose and lipid homeostasis. We found that ‘triple treatment’ increased both active and total GLP1 and protected against olanzapine-induced perturbations in lipid and glucose metabolism under glucose stimulated conditions and this was paralleled by an attenuation in the olanzapine induced increase in the glucagon:insulin ratio. Our findings provide evidence that pharmacological approaches to increase endogenous GLP1 could be a useful adjunct approach to reduce acute olanzapine-induced perturbations in lipid and glucose metabolism.